2015
DOI: 10.5194/gmdd-8-2313-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and application of the WRFPLUS-Chem online chemistry adjoint and WRFDA-Chem assimilation system

Abstract: Abstract. Here we present the online meteorology and chemistry adjoint and tangent linear model, WRFPLUS-Chem, which incorporates modules to treat boundary layer mixing, emission, aging, dry deposition, and advection of black carbon aerosol. We also develop land surface and surface layer adjoints to account for coupling between radiation and vertical mixing. Model performance is verified against finite difference derivative approximations. A second order checkpointing scheme is created to reduce computational … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It highlights the necessity of the serious attention to local environmental conditions as well as the cooperation with ground inspection and patrols for instantaneous wildfire assessment and design of fire prevention policies and measures in a region. Additionally, the MODIS fire products are widely used as fire-location inputs for various dynamic global vegetation models (DGVMs) and general circulation models (GCMs) while the fire related uncertainties have already been discussed [68,69]. For example, Veira et al [69] applied MOD14A1 data to the GCM ECHAM6-HAM2 to simulate global patterns in the wildfire-caused emissions, and found that important omission biases may be introduced by the uncertainties in MODIS fire products.…”
Section: Discussionmentioning
confidence: 99%
“…It highlights the necessity of the serious attention to local environmental conditions as well as the cooperation with ground inspection and patrols for instantaneous wildfire assessment and design of fire prevention policies and measures in a region. Additionally, the MODIS fire products are widely used as fire-location inputs for various dynamic global vegetation models (DGVMs) and general circulation models (GCMs) while the fire related uncertainties have already been discussed [68,69]. For example, Veira et al [69] applied MOD14A1 data to the GCM ECHAM6-HAM2 to simulate global patterns in the wildfire-caused emissions, and found that important omission biases may be introduced by the uncertainties in MODIS fire products.…”
Section: Discussionmentioning
confidence: 99%
“…WRF‐TEB is developed using WRF‐CMake version 4.1.5 (Riechert & Meyer, 2019a, 2020; Table 1) as it adds CMake (Kitware Inc., 2019a) support to the latest versions of WRF to simplify the configuration and build process of WRF and WPS (WRF Preprocessing System). Although, WRF‐CMake version 4.1.5 does not include support for WRF‐Chem (Grell et al., 2005), WRF‐DA (Huang et al., 2009), WRFPLUS (Guerrette & Henze, 2015), or WRF‐Hydro (Gochis et al., 2018), its benefits may outweigh these limitations to model developers, code maintainers, and end‐users wishing to build WRF, as it includes: robust incremental rebuilds, dependency analysis of Fortran code, flexible library dependency discovery, integrated support for shared (Open Multi‐Processing; OpenMP) and distributed (Message Passing Interface; MPI) memory, support for automated testing using continuous integration (CI), and availability of experimental prebuilt binary releases for Linux, macOS, and Windows from the project's GitHub page or through the integration with GIS4WRF (Meyer & Riechert, 2019a), a QGIS (QGIS Development Team, 2019) toolkit for preprocessing and postprocessing, visualizing, and running simulations in WRF. Here we refer to both the physical model and the software (i.e., WRF‐CMake) as WRF, unless highlighting specific software features.…”
Section: Models and Softwarementioning
confidence: 99%
“…Adjoint models trace back influences (sensitivities) from a predefined receptor area to each source location at preceding timesteps, backward in time. While adjoint versions have been developed for a number of CTMs (Elbern and Schmidt, 1999;Guerrette and Henze, 2015;Hakami et al, 2005;Hakami et al, 2007;Henze et al, 2007;Martien et al, 2006;Mallet and Sportisse, 2005;Menut et al, 2000;Menut, 2003;Sandu et al, 2005;Zhao et al, 2020), most health-based applications of the adjoint method have been limited to GEOS-Chem and CMAQ models Hakami, 2013a, 2013b;Koo et al, 2013;Pappin et al, 2015Nawaz et al, 2021;Qu et al, 2022). GEOS-Chem is a global model, and as such most of the health-based applications of its adjoint have been at the global scale, while higher-resolution GEOS-Chem simulations have been applied at regional-to-continental scales in the U.S. and elsewhere in the world.…”
Section: Introductionmentioning
confidence: 99%